Effects of titanium and oxygen content on microstructure in low carbon steels - Lee, SY; Oh, YJ; Yi, KW (JAPAN INST METALS & MATERIALS, 2002)
The effects of the titanium and oxygen concentration on the characteristics of inclusions and microstructure in low carbon wrought steels were investigated. Increasing the titanium concentration from 48 to 120 ppm promoted the formation of TiN particles and decreased the prior austenite grain size. The fraction of intragranular ferrite in the microstructure A as relatively unchanged, When the oxygen concentration was increased from 50 to 130 ppm, the volume fraction and the number of inclusion increased. However. the fraction of intragranular ferrite in microstructures decreased abruptly above 80 ppm because the allotriomorph ferrite phase at the prior austenite grain boundary began to form.
Keywords: HEAT-AFFECTED ZONE; ACICULAR FERRITE; NONMETALLIC INCLUSIONS; COOLING RATE; WELD; TOUGHNESS; SOLIDIFICATION